Circulating Blasts and Associated Hematologic Disorders in Neonates with Down Syndrome - Jackson, Gregory L.; Sendelbach, Dorothy M.; Rambally, Brooke; Manning, M. Denise; Engle, William D. (American Journal of Perinatology, 2012)
We analyzed complete blood count (CBC) data obtained from neonates with Down syndrome (DS) in a primarily Hispanic population over a 10-year period to determine the incidence of hematologic abnormalities and the relationship of abnormalities to the presence of circulating blasts (CB). Hematologic values obtained during the first 10 days were analyzed. Definitions were: CB, ≥ 1% blasts manually counted on peripheral smear; elevated white blood cell count (WBC), >30,000 cells/mm3; thrombocytopenia, platelet count < 150,000/mm3; polycythemia, hematocrit >65%. Two hundred thirty-two neonates (88% Hispanic) with DS had 692 CBCs available for analysis. The presence of CB (11.6%) and the incidence of thrombocytopenia (60.2%) were significantly higher in DS neonates than in the reference group. Elevated WBC (33.3%) and thrombocytopenia (84.6%) were more common in DS neonates with CB versus those with no CB. No relationship between thrombocytopenia and polycythemia was observed. Unlike previous reports, we did not observe a male predominance in those DS neonates with CB. Thrombocytopenia occurred frequently in DS neonates and was significantly more likely in those with CB than in those with no CB. CBC screening should be performed routinely in DS neonates.
Keywords: myeloproliferative disorder; megakaryoblasts; thrombocytopenia; transient leukemia; polycythemia